2015
DOI: 10.4238/2015.april.27.22
|View full text |Cite
|
Sign up to set email alerts
|

A new repertoire of informations about the quorum sensing system in Salmonella enterica serovar Enteritidis PT4

Abstract: ABSTRACT. Salmonella spp are among the main causative agents of foodborne diseases. Some phenotypes associated with increased drug resistance and virulence are regulated by quorum sensing (QS). In the present study, the autoinducer (AI)-1-and -2-mediated QS mechanisms were characterized in Salmonella enterica serovar Enteritidis PT4 for the first time. Salmonella Enteritidis did not produce AI-1. Phylogenetic analysis of nucleotides encoding the SdiA protein, the response regulator of AI-1-mediated QS, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…On the other hand, the thiol proteins and thiol could prevent structural alterations of the SdiA protein caused by ROS/RNS. This rationale is possible because the cysteine residues (C) and their respective positions (C45, C122, C142, and C232) present in the SdiA protein of Salmonella Enteritidis PT4 578 could be susceptible to oxidative stress [ 105 ]. The C232 is the main conserved residue among LuxR family proteins [ 31 ] and it is involved in the interaction between the Ligand-binding domain (LBD) with DNA-binding domain (DBD) and DBD-DBD [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the thiol proteins and thiol could prevent structural alterations of the SdiA protein caused by ROS/RNS. This rationale is possible because the cysteine residues (C) and their respective positions (C45, C122, C142, and C232) present in the SdiA protein of Salmonella Enteritidis PT4 578 could be susceptible to oxidative stress [ 105 ]. The C232 is the main conserved residue among LuxR family proteins [ 31 ] and it is involved in the interaction between the Ligand-binding domain (LBD) with DNA-binding domain (DBD) and DBD-DBD [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The choice of C12-HSL was based on studies showing its increased effect on biofilm formation by Salmonella compared to other AHLs with shorter carbon chains due to its higher affinity to SdiA. The concentration too was based on those same studies ( Campos-Galvão et al, 2015 , 2016 ; Almeida et al, 2016 , 2017b , 2018 ). The acetonitrile concentration was less than 1% (vol/vol) in the culture medium since according to Michael et al (2001) , this concentration does not exhibit an effect on the growth and response of Salmonella to AHL.…”
Section: Methodsmentioning
confidence: 99%
“…This could be explained by its higher binding affinity to the SdiA protein when compared to other AHLs through molecular docking studies ( Almeida et al, 2016 ). Besides C12-HSL, other AHLs tested did not influence the growth of Salmonella Enteritidis PT4 578 cultivated in anaerobic Tryptic Soy Broth (TSB) medium at 37°C ( Campos-Galvão et al, 2015 ; Almeida et al, 2017b ). Cultivation of Salmonella Enteritidis PT4 578 in anaerobic TSB medium supplemented with C12-HSL also led to alterations in protein abundance and levels of organic acids associated with the early stationary phase of growth ( Almeida et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…enterica serovar Enteritidis phagotype PT4 578, which was isolated from chicken breasts was used, courtesy of the Oswaldo Cruz Foundation – FIOCRUZ (Rio de Janeiro, Brazil). The QS mechanism of this isolate was characterized previous . The stock cultures were performed in Luria Bertani broth (LB) (tryptone 1%, yeast extract 0.5% and NaCl 0.4%), pH 7.4, containing 20% (v/v) sterile glycerol and were frozen at 20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Michael et al confirmed that SdiA is used to detect only signals from other bacterial species because of the lack of the gene encoding the AHL synthase in the E. coli and Salmonella Typhimurium genomes. Phylogenetic analysis of nucleotides encoding the SdiA protein, and comparative alignment of its amino acids showed that the gene and protein are conserved in Salmonella but this pathogen also failures to produce the signal molecule AHL . Genetic screening identify that four genes, srgA , srgB , srgC , and rck , in the pSLT plasmid encoding virulence genes in Salmonella Typhimurium were dependent on the expression of sdiA .…”
Section: Introductionmentioning
confidence: 99%